Corporate culture and closure at Pepsi Cola - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case study examines an account of the corporate culture at Pepsi Cola, as told by one of the company's former vice-presidents, John Sculley. Sculley's account could be seen as biased or self-promoting. However, it does provide unique insight into the corporate culture at Pepsi Cola in the late 1970s, in terms of values, norms, symbolism and understandings.